Synthetic biology for a promising future (Invited Lecture) - Rodrigues, Joana Lúcia Lima Correia (2023)
In this invited lecture, Synthetic Biology is presented as a powerful technology to solve many problems in different fields. After discussing several synthetic biology methods and tools, applications in several industries (chemical, food, pharmaceutical), environment, and health (vector control and treatment) were presented. Additionally, synthetic biology concerns and containment strategies were also discussed.